Examination of data citation guidelines in style manuals and data repositories. Issue 2 (16th December 2020) - Yoon, JungWon; Chung, EunKyung; Schalk, Janet; Kim, Jihyun
Abstract: This study investigated the status of data citation guidelines by analysing 15 style manuals and 100 data repositories in various fields. Analysis results are presented through a comparison with eight items in the Joint Declaration of Data Citation Principles (JDDCP). Only nine style manuals and only 20 repositories contain instructions regarding data citation. The guidelines generally agree on the importance of the author, publication date, title, and publisher, but there is large variation between the different guides. Analysis of the guidelines revealed that they generally reflect the principles of the JDDCP. In particular, the principle of Credit and Attribution is significantly reflected in style manuals and data repositories and supports one of the major motivations for data sharing. The principles of Unique Identification, Access, and Persistence are less well supported in data citation guidelines. However, the principles of Importance, Evidence, Specificity and Verifiability, and Interoperability and Flexibility are rarely supported. The findings of this study reveal that better guidelines are required, and future work could investigate developing and assessing the standard guidelines for data citation in different fields.